Uji Potensi Fungi Pelapuk Putih Pada Kayu Karet Lapuk (Hevea brasilliensis Muell. Arg) Sebagai Pendegradasi Lignin Test of Potential White Rot Fungi at Rotten Karet Wood (Hevea bresilliensis Muell. Arg) as degrading lignin - Gusti Prabu Jaya P; Edy Batara Mulya Siregar; Nelly Anna (Program studi Kehutanan USU, 2015)
Lignin is a natural polymer and an important compound of plant cell wall constituent. The research objective to get white rot wood in the Rotten Karet Wood, measure the activity of lignin peroxidase at White Rot Fungi, and know the potential of White Rot Fungi for biopulping. The samples taken at Karet land in Arboretum USU. The Bavendamm and lignolitic enzyme activities test found three species of fungus that came from genus Phanerochaete sp1, Phanerochaete sp2, dan Exidia sp. The highest activity of lignin peroxidase was produced by Phanerochaete sp2 isolate by the value of 0,466 U/ml. Key word : karet wood, white rot fungi, lignin peroxidase, bavendamm test.